Chapter Along the Caeretan coast and forward on - Tartara, Patrizia (Proceedings e report, 2020)
The territory along the coast north-west of Ro me, still well preserved; in the Etruscan period was for the most under Caere control; it had the three important ports. The territory of Caere has been analyzed for a long time now, through an historical-topographic analytical study of the traces of archaeological remains. The research has been carried out by use of historical and recent aerial photographs and glass slides, last but not least the contribution of the monitoring aerial flights operated with the Carabinieri Helicopter Group of Pratica di Mare.